The promotion action of AURKA on post-ischemic angiogenesis in diabetes-related limb ischemia - Tao Bai; Mingxing Li; Yuanfeng Liu; Zhentao Qiao; Xusheng Zhang; Yafeng Wang; Zhiwei Wang (Molecular Medicine, 2023)
Abstract Background Diabetes-related limb ischemia is a challenge for lower extremity amputation. Aurora Kinase A (AURKA) is an essential serine/threonine kinase for mitosis, while its role in limb ischemia remains unclear. Method Human microvascular endothelial cells (HMEC-1) were cultured in high glucose (HG, 25 mmol/L d-glucose) and no additional growth factors (ND) medium to mimic diabetes and low growth factors deprivation as in vitro model. Diabetic C57BL/6 mice were induced by streptozotocin (STZ) administration. After seven days, ischemia was surgically performed by left unilateral femoral artery ligation on diabetic mice. The vector of adenovirus was utilized to overexpress AURKA in vitro and in vivo. Results In our study, HG and ND-mediated downregulation of AURKA impaired the cell cycle progression, proliferation, migration, and tube formation ability of HMEC-1, which were rescued by overexpressed AURKA. Increased expression of vascular endothelial growth factor A (VEGFA) induced by overexpressed AURKA were likely regulatory molecules that coordinate these events. Mice with AURKA overexpression exhibited improved angiogenesis in response to VEGF in Matrigel plug assay, with increased capillary density and hemoglobin content. In diabetic limb ischemia mice, AURKA overexpression rescued blood perfusion and motor deficits, accompanied by the recovery of gastrocnemius muscles observed by H&E staining and positive Desmin staining. Moreover, AURKA overexpression rescued diabetes-related impairment of angiogenesis, arteriogenesis, and functional recovery in the ischemic limb. Signal pathway results revealed that VEGFR2/PI3K/AKT pathway might be involved in AURKA triggered angiogenesis procedure. In addition, AURKA overexpression impeded oxidative stress and subsequent following lipid peroxidation both in vitro and in vivo, indicating another protective mechanism of AURKA function in diabetic limb ischemia. The changes in lipid peroxidation biomarkers (lipid ROS, GPX4, SLC7A11, ALOX5, and ASLC4) in in vitro and in vivo were suggestive of the possible involvement of ferroptosis and interaction between AUKRA and ferroptosis in diabetic limb ischemia, which need further investigation. Conclusions These results implicated a potent role of AURKA in diabetes-related impairment of ischemia-mediated angiogenesis and implied a potential therapeutic target for ischemic diseases of diabetes.